Mesyuarat Akademik bil. 2/2024 - UiTM, AAGBS (Arshad Ayub Graduate Business School (AAGBS), 2024)
On 7 October 2024, Arshad Ayub Graduate Business School (AAGBS) UITM held Mesyuarat Akademik Bil. 2/2024 at Dewan Kuliah A, Fakulti Pengurusan dan Perniagaan, UiTM Shah Alam. The meeting provided a structured platform for academic leaders and staff to review academic performance, discuss key operational matters, and align strategies for the continuous improvement of academic programmes and service delivery. It also supported effective coordination among departments and strengthened decision-making processes in line with UiTM's academic governance framework. Through this meeting, AAGBS reinforced its commitment to academic quality, accountability, and institutional effectiveness.